The economy of Puerto Rico : restoring growth - Collins, Susan Margaret; Bosworth, Barry, 1942-; Soto-Class, Miguel A. (Center for the New Economy ; Brookings Institution Press, 2006)
In this innovative new book, economists from U.S. and Puerto Rican institutions address a range of major policy issues affecting the islands economic development. To frame the current situation, the contributors begin by assessing Puerto Ricos past experience with various growth policies.